2008
DOI: 10.1111/j.1365-2664.2007.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of grazing intensity and landscape composition on the diversity and abundance of flower‐visiting insects

Abstract: Summary 1.The loss of semi-natural grasslands in agro-ecosystems has increased the importance of adequate management of remaining grasslands. Recommendations for intensive grazing have been debated because the effects of different management practices may differ between taxa and species. The increased fragmentation of grasslands suggests that the influence of management practices should be studied in a landscape context. 2. We studied four groups of flower visitors, many of which are pollinators, bees (Apoidea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
134
3
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 54 publications
8
134
3
5
Order By: Relevance
“…This contrasts with some other common bumble bee species, such as B. bifarius, which showed no response to grazing intensity. The few studies that have examined the effect of grazing intensity on the species composition of bumble bees demonstrated that species responses are varied (Carvell 2002, Sjö din 2007, Sjö din et al 2008. Differences in sensitivity to grazing may be driven by differences in life history, including morphology associated with foraging strategy (e.g., tongue length) and different requirements for nesting (Goulson 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with some other common bumble bee species, such as B. bifarius, which showed no response to grazing intensity. The few studies that have examined the effect of grazing intensity on the species composition of bumble bees demonstrated that species responses are varied (Carvell 2002, Sjö din 2007, Sjö din et al 2008. Differences in sensitivity to grazing may be driven by differences in life history, including morphology associated with foraging strategy (e.g., tongue length) and different requirements for nesting (Goulson 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work on native bees suffers from some limitations common in many livestock grazing studies. First, most studies have been observational (i.e., they have not experimentally manipulated grazing level), and thus lack the ability to infer a causal relationship (e.g., Sugden 1985, Carvell 2002, Kruess and Tscharntke 2002, Vulliamy et al 2006, Hatfield and LeBuhn 2007, Sjö din 2007, Sjö din et al 2008, Xie et al 2008, Kearns and Oliveras 2009. Second, many studies have compared only the presence or absence of grazing (e.g., Sugden 1985, Xie et al 2008, rather than a gradient of grazing intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the number of spiders is reduced by mowing in the long term. However, due to the high number of inflorescences, especially flower visiting insects are favoured by this habitat (Sjödin, 2007;Sjödin et al, 2008) if the mowing regime is adjusted to their requirements: mowing of neighbouring areas at different times.…”
Section: Extensively Used Meadowsmentioning
confidence: 99%
“…Actually, different taxonomic groups may respond to different land use types or changing land use intensities in idiosyncratic ways. For example, plant diversity may be maximized under higher grazing intensities than insect diversity (Pöyry et al 2004(Pöyry et al , 2006van Klink et al 2015), and among arthropods optimal intensities may also differ (Sjödin et al 2008). Switching from grazing to mowing, or to other types of surrogate usage, may either have beneficial (Socher et al 2013), detrimental (Catorci et al 2014) or neutral (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a corollary, the 'optimal' management appears highly group-specific, and for conserving cross-taxonomic species richness, diversifying management regimes has hence repeatedly been recommended (e.g. Baur et al 2006;Berg et al 2011;Sjödin et al 2008).…”
Section: Introductionmentioning
confidence: 99%